Reliability of high-density surface electromyography for assessing characteristics of the thoracic erector spinae during static and dynamic tasks. (December 2022) - van Helden, J.F.L.; Martinez-Valdes, E.; Strutton, P.H.; Falla, D.; Chiou, S.Y.
Abstract: Purpose: To establish intra- and inter-session reliability of high-density surface electromyography (HDEMG)-derived parameters from the thoracic erector spinae (ES) during static and dynamic goal-directed voluntary movements of the trunk, and during functional reaching tasks. Methods: Twenty participants performed: 1) static trunk extension, 2) dynamic trunk forward and lateral flexion, and 3) multidirectional functional reaching tasks on two occasions separated by 7.5 ± 1.2 days. Muscle activity was recorded bilaterally from the thoracic ES. Root mean square (RMS), coordinates of the barycentre, mean frequency (MNF), and entropy were derived from the HDEMG signals. Reliability was determined with intraclass correlation coefficient (ICC), coefficient of variation, and standard error of measurement. Results: Good-to-excellent intra-session reliability was found for all parameters and tasks (ICC: 0.79-0.99), whereas inter-session reliability varied across tasks. Static tasks demonstrated higher reliability in most parameters compared to functional and dynamic tasks. Absolute RMS and MNF showed the highest overall reliability across tasks (ICC: 0.66-0.98), while reliability of the barycentre was influenced by the direction of the movements. Conclusion: RMS and MNF derived from HDEMG show consistent inter-session reliability in goal-directed voluntary movements of the trunk and reaching tasks, whereas the measures of the barycentre and entropy demonstrate task-dependent reliability.